Fenomena Neologisme dalam Bahasa Gaul Generasi Z di Media Sosial - Iftina Humaimah; Nesya Aulia; Asy Syifa Anhar Sunarko; Encep Kusumah (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
Advances in digital technology and globalization have opened up new communication spaces that shape the way Generation Z speaks, who not only play the role of language users but also as creators and spreaders of new vocabulary or neologisms. This research aims to recognize, classify, and examine the phenomenon of neologisms in Generation Z slang on the TikTok and X platforms through a descriptive qualitative approach with free tapping and watching techniques. Different from previous studies that generally only focused on one type of neologism or one specific platform, the novelty of this research lies in the analysis of various types of neologisms simultaneously from two platforms at once so as to produce a more comprehensive picture of the dynamics of the formation of new vocabulary in digital communication. The results of the analysis found four patterns of neologism formation that are actively used, namely absorption from foreign languages, abbreviations and acronyms, syllable reversals, and shifts in meaning, all of which follow systematic morphological rules as reflected in words such as roasting, mager, gercep, mantul, kuy, sultan, and gas. This study concludes that Generation Z slang is an expression of linguistic creativity born from the need for identity and social solidarity in the digital era, while emphasizing that social media has become a linguistic arena that accelerates the spread of neologisms as part of the face of the Indonesian language that continues to develop dynamically in today's digital space.